Commissive Speech Act in Job Interview: How Applicants Depict Good Leader Characters in Response to Situational Questions - Farida Indri Wijayanti; Djatmika Djatmika; Sumarlam Sumarlam; FX. Sawardi (Universitas Sebelas Maret, 2022)
In job interview, applicants are occasionally asked to visualize an imaginery job scenario and explain what they will do in that situation. Similarly, in interview and public test of Corruption Eradication Comission (KPK), leader candidates were asked such kind of situational questions. Their selection of responses for such question will reveal who they are. They can portray not only the job competencies but also good characters in leadership. Data in the form of commissive utterances were collected from interviews involving leader candidates of KPK obtained from the Ministry of State Secretariat of the Republic of Indonesia's Youtube channel. In the corpus, promising acts were identified as the most-used commissive speech act in response to situational questions. Female candidates more frequently implemented commissive than male. There were three forms of commissive speech act in the interview test, namely: making a promise, expressing capability, and intent. With commissive speech act, the finding further revealed that both female and male candidate leaders showed elemen characters such as passionate, demonstrative initiative, strive for excellence, collegial, continuous learner, transparent, socially responsible, accepts consequences, brave, confident, purposive, future-oriented, optimistic, and creative.